2016
DOI: 10.1186/s13071-016-1369-9
|View full text |Cite
|
Sign up to set email alerts
|

Do schistosome vaccine trials in mice have an intrinsic flaw that generates spurious protection data?

Abstract: The laboratory mouse has been widely used to test the efficacy of schistosome vaccines and a long list of candidates has emerged from this work, many of them abundant internal proteins. These antigens do not have an additive effect when co-administered, or delivered as SWAP homogenate, a quarter of which comprises multiple candidates; the observed protection has an apparent ceiling of 40–50 %. We contend that the low level of maturation of penetrating cercariae (~32 % for Schistosoma mansoni) is a major limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 102 publications
1
71
0
Order By: Relevance
“…For instance, the resistance against schistosomiasis in individuals that are naturally resistant to schistosome infection (Endemic normal) is associated with Th1 immune response as demonstrated by high level production of interferon gamma (IFN-γ) by peripheral blood mononuclear cells (PBMCs) from these individuals stimulated with schistosome antigens (McManus and Loukas 2008; Viana et al 1994). Furthermore, studies with RA vaccine showed that schistosomulae are killed in the lungs of protected animals as a result of inflammation (Wilson et al 2016). In the RA model, co-administration of IL-12 (a potent Th1 inducing cytokine) with RA vaccine resulted in almost sterile immunity which was associated with a high induction of IFN-γ in an autocrine manner (Wilson and Coulson 2009; Wilson et al 1999; Wilson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the resistance against schistosomiasis in individuals that are naturally resistant to schistosome infection (Endemic normal) is associated with Th1 immune response as demonstrated by high level production of interferon gamma (IFN-γ) by peripheral blood mononuclear cells (PBMCs) from these individuals stimulated with schistosome antigens (McManus and Loukas 2008; Viana et al 1994). Furthermore, studies with RA vaccine showed that schistosomulae are killed in the lungs of protected animals as a result of inflammation (Wilson et al 2016). In the RA model, co-administration of IL-12 (a potent Th1 inducing cytokine) with RA vaccine resulted in almost sterile immunity which was associated with a high induction of IFN-γ in an autocrine manner (Wilson and Coulson 2009; Wilson et al 1999; Wilson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies with RA vaccine showed that schistosomulae are killed in the lungs of protected animals as a result of inflammation (Wilson et al 2016). In the RA model, co-administration of IL-12 (a potent Th1 inducing cytokine) with RA vaccine resulted in almost sterile immunity which was associated with a high induction of IFN-γ in an autocrine manner (Wilson and Coulson 2009; Wilson et al 1999; Wilson et al 2016). Studies by our group and other colleagues have shown that the production of IFN-γ is associated with protection against schistosome infection in animal models (Ahmad et al 2009c; Le et al 2014; Pearson et al 2012; Varaldo et al 2004; Zhang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of antigens have been identified, some of which confer protection of varying degrees and are considered promising though they do not quite reach the level of immunity elicited following vaccination with irradiated cercariae [34;35]. With the exception of a few antigens, the prophylactic efficacy of these antigens has been evaluated only in the murine model which inherently has an apparent ceiling of 40-50% protection [34].…”
Section: Current Status Of Schistosomiasis Vaccinesmentioning
confidence: 99%
“…Hundreds of antigens have been identified, some of which confer protection of varying degrees and are considered promising though they do not quite reach the level of immunity elicited following vaccination with irradiated cercariae [34;35]. With the exception of a few antigens, the prophylactic efficacy of these antigens has been evaluated only in the murine model which inherently has an apparent ceiling of 40-50% protection [34]. Recently, it has been argued with convincing arguments that the low level of maturation of penetrating cercariae (~32% for Schistosoma mansoni) is a major limitation of the model since 68/100 parasites fail to mature in naïve mice due to natural causes [34].…”
Section: Current Status Of Schistosomiasis Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation